Brain-Based Learning: The Impact on Student’s Higher Order Thinking Skills and Motivation - Permana, Ardian Agus; Kartika, Ika (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
The research objectives are to determine the effects of the Brain-based Learning (BBL) approach on students' higher-order thinking skills and student motivation to learn physics. This research used the quasi-experimental pretest-posttest design. The sample of this research consisted of two tenth-grade science classes chosen by simple random sampling technique. This research population was all tenth-grade students of a senior high school in Yogyakarta. The data were obtained by test and non-test techniques. The result shows that BBL approach affects on the students' higher-order thinking skills (sig. 2-tailed = 0,003 <α = 0.05). Further, it also improves students' higher-order thinking skills represented by the N-Gain value (experimental class N-Gain = 0.40 > control class N-Gain = 0.21). On the other hand, not only on student's higher-order thinking skills, BBL approach bring the significant effect on students’ motivation in learning physics (sig. 2-tailed = 0,000 <α = 0.05) as well as could improve it (experimental class N-Gain = 0.55 > control class N-Gain = 0.04). It means that the BBL approach could improve higher-order thinking skills and students' motivation more effectively than the traditional approach